2012
DOI: 10.1038/nmeth.1903
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, efficient inhibition of microRNA function in mice using rAAV vectors

Abstract: Understanding the function of individual microRNA (miRNA) species in mice would require the production of hundreds of loss-of-function strains. To accelerate analysis of miRNA biology in mammals, we combined recombinant adeno-associated virus (rAAV) vectors with miRNA `Tough Decoys' (TuDs) to inhibit specific miRNAs. Intravenous injection of rAAV9 expressing anti-miR-122 or anti-let-7 TuD depleted the corresponding miRNA and increased its mRNA targets. rAAV producing anti-miR-122—but not anti-let-7—TuD reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
191
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(199 citation statements)
references
References 30 publications
7
191
0
1
Order By: Relevance
“…98 Notably, a novel kind of sponges called anti-miRs is becoming a strong candidate for miRNA-based therapeutics. 43,[99][100][101][102][103][104][105][106][107] The anti-miRs are chemically modified oligonucleotides developed to modulate the activities of specific miRNAs. A recent study carried out by Hogan and his colleagues 108 demonstrated that the anti-miR physically associated with the AGO protein complex in the context of the cognate target miRNA both in vitro and in vivo.…”
Section: Degradome-seqmentioning
confidence: 99%
“…98 Notably, a novel kind of sponges called anti-miRs is becoming a strong candidate for miRNA-based therapeutics. 43,[99][100][101][102][103][104][105][106][107] The anti-miRs are chemically modified oligonucleotides developed to modulate the activities of specific miRNAs. A recent study carried out by Hogan and his colleagues 108 demonstrated that the anti-miR physically associated with the AGO protein complex in the context of the cognate target miRNA both in vitro and in vivo.…”
Section: Degradome-seqmentioning
confidence: 99%
“…Such adaptations of the miRNA sponge concept allow longer-term inhibition of miRNAs than can be achieved by transient transfection of RNA polymerase II sponge reporter vectors or modified RNA oligonucleotides. Xie et al (2012) combined recombinant adeno-associated virus (rAAV) vectors with miRNA TuDs to inhibit specific miRNAs. Injection of a rAAV9 construct expressing anti-miR-122 or anti-let-7 TuDs resulted in long-term depletion of the corresponding miRNA and increased expression of its mRNA targets.…”
Section: Mirna Sponges/decoysmentioning
confidence: 99%
“…Studies have also shown that RNA polymerase II promoters can be used to efficiently express TuD inhibitors within the cell [24,25]. It has been shown that adeno-associated virus-delivered TuDs induced long-term miRNA inhibition in mice [27,28]. TuDs and sponges are both more effective when the miRNA binding sites are non-complementary to the target miRNA at position 10–11, presumably because Ago2-dependent cleavage of the TuD is prevented [23,25,29].…”
Section: Introductionmentioning
confidence: 99%
“…TuDs and sponges are both more effective when the miRNA binding sites are non-complementary to the target miRNA at position 10–11, presumably because Ago2-dependent cleavage of the TuD is prevented [23,25,29]. Whether TuD activity is mediated by miRNA sequestration alone, or also by miRNA degradation remains unclear, since several studies have reported conflicting results [20,23,27]. In comparative studies, TuDs proved more effective miRNA inhibitors than sponges [23,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation